Existence and survival of the rural family textile micro-enterprise of San Rafael Ixtapalucan, Puebla, Mexico - Hernández Romero, Oliverio; Soriano Hernández, María Guadalupe (Revista Mexicana de Ciencias Agrícolas, 2017)
Each family is different and therefore the needs both  individual and collective are also different in nature;  among them the basis for the existence and survival of the  San Rafael Ixtapalucan Rural Family Microenterprise can  be found, which emerges with an entrepreneur initiative  based on a business idea whose incidence in the market is  low. The objective is to determine if the human needs of  the family group are linked to the existence and survival of  the rural family textile micro-enterprise (MEFRT). Results  show that MEFRT is a viable strategy for the satisfaction of  the basic needs of the family group, however, it also shows  that it is an entity that has serious difficulties regarding its  survival.
Keywords: family; family microenterprise; human needs; satisfactory